Caminhos para uma proposta formativa docente para implementação de práticas interdisciplinares - Pantaleão, Jinlova de Oliveira (2021)
This research investigated the educator’s perceptions about interdisciplinary pedagogical practices and, for that purpose, it had as its main goal to analyze the educator’s perceptions about interdisciplinary pedagogical practices and as its specific goals: 1 – to identify the challenges they face in developing interdisciplinary practices at the classroom; and 2 - to elaborate formative principles that indicate the path to an interdisciplinary formative proposal. The research has taken a qualitative approach and the methods used to collect data were a survey applied to an entire pedagogical team at a state elementary school through Google Forms and a semi-structured interview with four teachers who work in the late stages of middle school and high school, also at the public educational system. The application of both these methods have occurred remotely due to the new Coronavirus pandemic. The authors that substantiated this research were Almeida (2004, 2005 2011, 2014), Fazenda (2002, 2011, 2012, 2013), Nóvoa (1995, 2017), Placco (2010), Pombo (1993, 2004) and Wallon (1975, 1995, 2010). The thesis has sought to comprehend how the development of this interdisciplinary body of work has taken place and how the educators have reproduced those practices alongside their peers and students. We hope, with this research, to be able to contribute to the reflections about the continuing education of these professionals, having in mind the development of an interdisciplinary practice within the context of basic schooling. It has been noted that within the scope of continuing education there are clear shortcomings of structural aspects and the need to reinforce the collective work